Public Policy Implementation: Study on Educational Budgeting of Palopo - Ahyar Amir (Journal La Sociale, 2020)
This study aims to analyze the content of the policy in the implementation of the Education Budget in the Palopo City Budget and to analyze the policy context in the implementation of Palopo Regional Educational Budgeting in the. This study uses a qualitative approach through the use of interviews, direct observation in the field and analysis of written materials as the main data source. From the research results obtained, the indicator of interest that is influenced shows the interests of the school become more attentive and more accommodated. Implementation of Free Education in the field where the school benefits in the form of the use of free education funds for additional incentives from teaching hours of teachers outside of school hours and additional operational costs, the use of free education at the elementary level more budget absorbed for intensive teachers and for junior high school budgets more absorbed in the costs of supporting school activities such as stationery for the office and teaching and learning activities. In the implementation of free education, the decision-making process is carried out through deliberations that involve all interested parties (students' parents through the school committee and the school itself). Characteristics that are different from each school makes it difficult for schools to implement free education programs. The existence of this free education program makes the active role of parents in paying attention to the learning of students to be reduced.